The safety of one-stage versus two-stage approach to osseointegrated prosthesis for limb amputation: a systematic review - Ella Banducci; Munjed Al Muderis; William Lu; Stephen R. Bested (Bone & Joint Open, 2023)
Aims: Safety concerns surrounding osseointegration are a significant barrier to replacing socket prosthesis as the standard of care following limb amputation. While implanted osseointegrated prostheses traditionally occur in two stages, a one-stage approach has emerged. Currently, there is no existing comparison of the outcomes of these different approaches. To address safety concerns, this study sought to determine whether a one-stage osseointegration procedure is associated with fewer adverse events than the two-staged approach. Methods: A comprehensive electronic search and quantitative data analysis from eligible studies were performed. Inclusion criteria were adults with a limb amputation managed with a one- or two-stage osseointegration procedure with follow-up reporting of complications. Results: A total of 19 studies were included: four one-stage, 14 two-stage, and one article with both one- and two-stage groups. Superficial infection was the most common complication (one-stage: 38% vs two-stage: 52%). There was a notable difference in the incidence of osteomyelitis (one-stage: nil vs two-stage: 10%) and implant failure (one-stage: 1% vs two-stage: 9%). Fracture incidence was equivocal (one-stage: 13% vs two-stage: 12%), and comparison of soft-tissue, stoma, and mechanical related complications was not possible. Conclusion: This review suggests that the one-stage approach is favourable compared to the two-stage, because the incidence of complications was slightly lower in the one-stage cohort, with a pertinent difference in the incidence of osteomyelitis and implant failure. Cite this article: Bone Jt Open 2023;4(7):539–550.